At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
[tex]f(u) = u[/tex]
Step-by-step explanation:
Given
[tex]\int {\ln(u)} \, du = u[\ln(u) - f(u)] + c[/tex]
Required
Find f(u)
To do this, we start by integrating the left-hand side
[tex]\int {\ln(u)} \, du = u\ln(u) - f(u)+ c[/tex]
Using integration by parts, we have:
[tex]\int {fg'} = fg - \int f'g[/tex]
So, we have:
[tex]f = \ln(u)[/tex]
Differentiate
[tex]f'=\frac{1}{u}[/tex]
[tex]g' = 1[/tex]
Integrate
[tex]g=u[/tex]
So:
[tex]\int {fg'} = fg - \int f'g[/tex]
[tex]\int \ln(u)\ du = \ln(u) * u - \int \frac{1}{u} * u\ du[/tex]
[tex]\int \ln(u)\ du = u\ln(u) - \int \ du[/tex]
So, we have:
[tex]u\ln(u) - \int \ du = u\ln(u) - f(u) + c[/tex]
Integrate du using constant rule
[tex]u\ln(u) - u + c = u\ln(u) - f(u) + c[/tex]
Subtract c from both sides
[tex]u\ln(u) - u = u\ln(u) - f(u)[/tex]
Subtract u ln(u) from both sides
[tex]- u = - f(u)[/tex]
Rewrite as:
[tex]f(u) = u[/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.